Synthesis and Characterization of Degradation‐Resistant Cu@CuPd Nanowire Catalysts for the Efficient Production of Formate and CO from CO2. Issue 12 (26th June 2019) - Hou, Yuhui; Erni, Rolf; Widmer, Roland; Rahaman, Motiar; Guo, Huizhang; Fasel, Roman; Moreno‐García, Pavel; Zhang, Yucheng; Broekmann, Peter
Abstract: Not only are the product selectivity and the activity of electrocatalysts important aspects for the evaluation of their overall performance, but also their stability and resistance against structural and compositional degradation during the electrocatalytic reaction. Palladium nanoparticles (Pd‐NPs) have already been identified as superior electrocatalysts for the electrochemical conversion of CO2 into formate at extremely low overpotentials and into carbon monoxide (CO) at medium overpotentials. However, these catalysts suffer from fast degradation, owing to irreversible CO poisoning of Pd reaction sites. Herein, we report on nanoparticulate bimetallic Pd45 Cu55 catalysts, demonstrating a similar selectivity and activity to the pure Pd‐NPs, but showing additional superior degradation stability and resistance against CO poisoning. Pd45 Cu55 catalysts were synthesized by means of a galvanic displacement reaction using copper nanowires (Cu‐NWs) as the starting material (template) for the galvanic displacement reaction, which leaves a surface‐confined alloy film and respective nanoparticles on the Cu‐NW template (denoted as Cu@CuPd‐NWs). A faradaic efficiency (FE) up to FEformate ≈80 % can be achieved at −0.3 V vs. RHE, thus clearly proving that the 'anomalous' CO2 reaction mechanism via the CO2 hydrogenation pathway, discussed for pure Pd‐NPs, can also be transferred to Pd‐based bimetallic systems. At medium overpotentials, the product selectivity changes from selective formate to predominant CO formation with a maximum faradaic efficiency of FECO =86 %. Extended CO2 electrolyses demonstrate, for both formate and CO production, superior degradation stability, for example, FECO remains at 85 %±5 % for the duration of 20 h. For the first time, identical location high‐angle annular dark‐field scanning transmission electron microscopy (IL‐HAADF‐STEM) in combination with energy‐dispersive X‐ray spectrometry and identical location scanning electron microscopy (IL‐SEM) were applied to demonstrate the compositional and structural stability of the bimetallic catalyst under CO2 reduction conditions. Abstract : Stability matters : Not only are the product selectivity and activity of electrocatalysts important aspects for the evaluation of their overall performance, but also their stability and resistance against structural and compositional degradation during the electrocatalytic reaction. Nanoparticulate bimetallic Pd45 Cu55 catalysts are reported, demonstrating a similar selectivity and activity to the pure Pd nanoparticles, but showing additional superior degradation stability and resistance against CO poisoning.